HRCT Pattern in COVID-19 Patients - Sohail Anwar, Faiza Farooq, Amir Waheed, Atif Masood, Tahir Ullah Khan, Faisal Amin Baig (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In December 2019, a group of cases of pneumonia of unknown cause was found in Wuhan, China, now known as coronavirus disease 2019, and the coronavirus was named severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). High-resolution computed1tomography (HRCT) is currently regarded as a significant imaging technique for aiding in the diagnosis & management of COVID-19 patients. Objective: To find the different patterns of1manifestation in HRCT chest in COVID-19 patients. Study Design: Descriptive Cross-Sectional Setting: University of Lahore Teaching Hospital, Lahore Methodology: A descriptive, cross-sectional study was conducted in Radiology Department in University of teaching hospital, Lahore. 240 participants’ medical histories were thoroughly reviewed, both directly from them and on case sheets. All patients with confirmed cases of COVID-19 pneumonia were admitted to the hospital and received a chest HRCT. Three follow-up HRCT chest scans were performed on one patient. The distribution and patterns of lung involvement were studied. Each of the five lung lobes was evaluated visually for degree of involvement and categorized as mild (26-50 percent), moderate (51-75 percent), or severe (75 percent) (76-100 percent). Data was analyzing in SPSS. Age was presented as mean + SD. Gender and other HRCT patterns were presented as frequency & percentage. Result: Total 240 COVID-19 patients included. There were 142(59.4%) male and 97(40.6%) female. The mean age was 54.0+15.71 with age range of 4 to 84 years. Large number of patients 114(47.7%) were in the age group 45-64 years. Ground glass opacity was the most common CT abnormality, with 236(99.2%) cases. Among them 49(20.5%) cases had GGO plus consolidations. Crazy paving pattern was seen in 136(56.9%) cases. Only 10(4.2%) patients with GGO pulmonary nodules and pleural effusion were involved. The majority of the patients had a fever 114(47.5%), while the least frequent symptom was a runny nose (7(2.9%). Conclusion: Pure GGO pneumonia is the most prevalent pattern of COVID-19 pneumonia seen on HRCT scans, GGO consolidation, with crazy paving with prominent distribution in the lung posterior & peripheral area.